2011
DOI: 10.12659/msm.881903
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human cytomegalovirus UL145 and UL136 genes in low-passage clinical isolates from infected Chinese infants

Abstract: SummaryBackgroundHuman cytomegalovirus (HCMV) is a leading cause of morbidity and mortality in immunocompromised individuals. The unique long b’ (ULB’) region of HCMV contains at least 19 open reading frames (ORFs); however, little is known about the function of UL145 and UL136. We characterized UL145 and UL136 in low-passage clinical isolates from Chinese infants.Material/MethodsThe clinical strains of HCMV were recovered from the urine from HCMV-infected infants. Human embryonic lung fibroblasts (HELFs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Recently, m 5 C methylation in eukaryotic cells has been identified to largely depend on the function of the known "writer" NSUN2, which functions as an mRNA methyltransferase (Bohnsack et al, 2019;Yang Y. et al, 2019). Moreover, it was reported that NSUN2 affects cell biological processes including cell proliferation, migration, and mRNA metabolism by regulating mRNA m 5 C modification (Wang et al, 2011;Courtney et al, 2019). Compared to that in HCs, the NSUN2 expression (including mRNA and protein) in CD4 + T cells of patients with SLE was significantly lower, which further confirmed the Bis-Seq data of overall m 5 C levels in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, m 5 C methylation in eukaryotic cells has been identified to largely depend on the function of the known "writer" NSUN2, which functions as an mRNA methyltransferase (Bohnsack et al, 2019;Yang Y. et al, 2019). Moreover, it was reported that NSUN2 affects cell biological processes including cell proliferation, migration, and mRNA metabolism by regulating mRNA m 5 C modification (Wang et al, 2011;Courtney et al, 2019). Compared to that in HCs, the NSUN2 expression (including mRNA and protein) in CD4 + T cells of patients with SLE was significantly lower, which further confirmed the Bis-Seq data of overall m 5 C levels in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…The most recently described member of HCMV-encoded DDB1/CRL-interacting proteins is pUL145. In contrast to the adjacent genes UL144 and UL146 , UL145 is highly conserved among different HCMV strains, suggesting its relevance for viral replication as well as the conservation of its interaction partner(s) [120,139,140,141]. The UL145 gene gives rise to monocistronic as well as polycistronic transcripts [141,142].…”
Section: Exploitation Of Ddb1 and Crls By Virusesmentioning
confidence: 99%
“…The prediction of motifs for posttranslational modifications suggested a protein kinase C phosphorylation motif and one or two casein kinase II phosphorylation site(s) [139,141]. Additionally, Wang et al proposed the existence of a zinc finger structure [140]. However, to our knowledge, a crystal structure is not yet available.…”
Section: Exploitation Of Ddb1 and Crls By Virusesmentioning
confidence: 99%
“…Mononuclear cells were isolated from the blood samples using TFicoll separation solution (Shanghai Hua Jing Biotech Company). The urine samples were centrifuged for 10 minutes at 1,500 rpm and then the sediment was collected [ 17 ]. The DNA from mononuclear cells and from the sediment of urine samples were extracted using a DNA extraction kit according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%